Reflections on the Involvement of Managers in Supporting Romanian Companies during the Pandemic COVID -19: Array - Bucăța, George (Acta Universitatis Danubius. Œconomica, 2021)
The wide spread of COVID -19 in Europe, which also affects Romania, and the increasingly stringent measures taken by experts to prevent negative consequences for citizens and the economy, raise a number of questions about the activities that need to be undertaken by companies to ensure compliance and those who are in a position to take these measures. Many businesses in Romania have already made a conscious effort to guard against the threat of COVID -19, whether by stopping movement altogether for an indefinite period of time, changing the way in which activities are carried out (e.g. only online now), or by working with notable safeguards to mitigate the threats.